THE EVALUATION OF THE BUSINESS PLAN OF UNIVERSITY ALUMNI USING CONTINUOUS IMPROVEMENT MINDSET CONCEPT - Ismawati, Anastasia Filiana (Review of Management and Entrepreneurship, 2019)
In the past, producers think only about the outcome of production, however, producers began to shift, as the need of customers must be in line with the purpose of the product or service that is produced. This phenomenon enables product and service suppliers to obtain new opportunities from the unfulfilled wants and needs of customers. One of the mindsets that can help excelling a business and controls business projects is continuous improvement mindset, which is a continuous revision of the operational activity of a business that can be implemented with the resources that the business owns. This study identified the effect of continuous improvement mindset on the business of alumni of University A located in Surabaya and University B located in Yogyakarta based on the teaching pattern that is received by the alumni. Data collection was done using interviews with alumni business. There is a similarity in continuous improvement mindset behavior between alumni of Universities A and B. Continuous improvement mindset is still implemented by both alumni from both universities. The research findings showed that the education in each study program and entrepreneurship teaching are interconnected. The control over alumni’s business project is positively impacting with the implementation of continuous improvement mindset. The implemented control can impact sales, operational system and the increase of customer service